2021
DOI: 10.21926/obm.genet.2102128
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gene Expression in Human Breast Cancer MCF7 and Prostate Cancer PC3 Cells by the Human Copper-Binding Peptide GHK-Cu.

Abstract: The human copper-binding peptide GHK-Cu is a naturally occurring small plasma tripeptide (glycyl-l-histidyl-l-lysine) with a high affinity for copper (2+). GHK-Cu has multiple biological effects. It is known to stimulate regeneration of skin, nervous tissue, bones, lungs and liver, protect liver from oxidative damage, restore activity of irradiated fibroblasts, reduce inflammation and increase levels of antioxidant enzymes. Recent studies established that GHK modulates activity of a number of genes. It has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In a study, it was reported that GHK reduce the viability of glioblastoma cells at higher concentrations while the viability of L929 cells stay the same as the control (21). In a study with GHK-Cu complex, gene effects on MCF-7 breast and PC3 prostate cancer cell lines were investigated (26). It is also known that the GHK-Cu complex provides regeneration of the lung and liver.…”
Section: Estrogen Receptor (Pdb Id: 1a52)mentioning
confidence: 99%
“…In a study, it was reported that GHK reduce the viability of glioblastoma cells at higher concentrations while the viability of L929 cells stay the same as the control (21). In a study with GHK-Cu complex, gene effects on MCF-7 breast and PC3 prostate cancer cell lines were investigated (26). It is also known that the GHK-Cu complex provides regeneration of the lung and liver.…”
Section: Estrogen Receptor (Pdb Id: 1a52)mentioning
confidence: 99%
“…The regenerative and protective actions mainly for the skin tissues make GHK-Cu(II) largely used for cosmetic applications. However, the biological effects exerted by GHK and GHK-Cu(II) are relevant to cancer [ 9 , 10 , 11 , 12 ], neurodegeneration disorders and cognitive health [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%